The Preparation and Chemistry of Oxadiazolinones and Oxadiazolines - Knittel, Peter (My University, 1975)
The objectives of this work were fourfold. Firstly, the oxidation of semicarbazones with lead tetraacetate was examined from the point of view of products and of mechanism, as related to the mechanisms of other lead tetraacetate oxidations of carbonyl derivatives. Secondly, the chemistry of the acetone semicarbazone oxidation product, 5,5-dimethyl-Δ³-1,3,4-oxadiazolin-2-one was investigated. Thirdly, the chemistry of the methyl Iithium addition product of 5,5-dimethyl-Δ³-1,3,4-oxadiazolin-2-one, 2-hydroxy-2,5,5-trimethyl-Δ³-1,3,4-oxadiazoline, was studied mainly from the aspect of its novel radical chain thermal decomposition. Fourthly, a general principle regarding radical pathways was put forward.
Keywords: Chemistry; Chemistry